PELATIHAN SISTEM DIGITAL UNTUK MENINGKATKAN KUALITAS LAYANAN PUBLIK DI DESA GEMEL KECAMATAN JONGGAT KABUPATEN LOMBOK TENGAH NUSA TENGGARA BARAT - Muhamad Yunus (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Digital transformation has become a strategic approach to improving the efficiency, transparency, and quality of public services at the village level. Desa Gemel, located in Jonggat Subdistrict, Central Lombok Regency, Nusa Tenggara Barat, still faces several challenges in public service delivery, including the use of manual administrative systems, limited digital competencies among village officials, and the underutilization of information technology. This community service activity aimed to enhance the capacity of village officials and service personnel through digital system training to support the improvement of public service quality. The methods employed included a needs assessment, training workshops, hands-on practice sessions, and post-training evaluation. The results indicated a significant improvement in participants’ understanding and technical skills in operating digital administrative systems, managing digital archives, and utilizing online-based public service platforms. The implementation of digital systems contributed to increased efficiency in administrative processes, improved service responsiveness, and strengthened transparency and accountability in village governance. These findings imply that structured and context-based digital system training plays an important role in enhancing public service quality and supporting sustainable digital governance at the village level.